KEPASTIAN HUKUM PERMULAAN MASA IDDAH CERAI TALAK (Studi Komparasi Antara Kompilasi Hukum Islam dan Madzhab Syafi’i) - Muhammad Nur Fikri Abdillah; Ahmad Ubaidi Hasbillah (JURNAL ILMIAH NUSANTARA, 2024)
Marriage is one of several contracts (in relationships between humans) and worship (in relationships with Allah SWT) which are both regulated in Islamic law and state law. Islamic religious law, which is based on the Koran and Sunnah, has regulated marriage in such a way that it can be understood by expert scholars in this field. Marriage is also regulated in Law no. 16 of 2019 concerning amendments to Law no. 1 of 1947 concerning Marriage. As a rule of law, Indonesian citizens must comply as much as possible both religiously and administratively with the state. The existence of marriage does not rule out the possibility of divorce. Divorce is the last resort that can be used if a partner is no longer compatible. Likewise, divorce is also regulated in religious law and state law. After a divorce, the woman undergoes an iddah period. The iddah period in Islamic law is calculated from the time the husband pronounces divorce. Meanwhile, in the state law, it is explained in the Compilation of Islamic Law, Article 153. This type of research is normative/library research, namely research by examining library materials, whether from UU, KHI, books, fiqh books or other sources that are appropriate to the topic being studied, where in this type of research the law is what is is in the book/text (law in book) and becomes an expected situation (das solen). Meanwhile, the research method is qualitative research. Qualitative research is research that is intended to understand the phenomena experienced by research subjects. From the results of this research, it can be concluded that the difference between the Compilation of Islamic Law and the Syafi'I Madzhab regarding the beginning of the iddah period for divorce and divorce lies in the time when the iddah period is calculated. The similarity is the mechanism for calculating the iddah period of women who are divorced.